Countee Cullen collected poems - Cullen, Countee 1903-1946 (American poets project, 2013)
A major and sometimes controversial figure of the Harlem Renaissance, Countee Cullen fused a mastery of the formal lyric with a passionate engagement with themes social, religious, racial, and personal in such books as Color, Copper Sun, and The Black Christ. Certain of his poems-- "Heritage," "Yet Do I Marvel" -- are widely celebrated, but much of Cullen's work remains to be discovered. This volume restores to print a body of work of singular intensity and beauty